Coral bleaching is linked to the capacity of the animal host to supply essential metals to the symbionts. (17th April 2018) - Ferrier‐Pagès, Christine; Sauzéat, Lucie; Balter, Vincent
Abstract: Massive coral bleaching events result in extensive coral loss throughout the world. These events are mainly caused by seawater warming, but are exacerbated by the subsequent decrease in nutrient availability in surface waters. It has therefore been shown that nitrogen, phosphorus or iron limitation contribute to the underlying conditions by which thermal stress induces coral bleaching. Generally, information on the trophic ecology of trace elements (micronutrients) in corals, and on how they modulate the coral response to thermal stress is lacking. Here, we demonstrate for the first time that heterotrophic feeding (i.e. the capture of zooplankton prey by the coral host) and thermal stress induce significant changes in micro element concentrations and isotopic signatures of the scleractinian coral Stylophora pistillata . The results obtained first reveal that coral symbionts are the major sink for the heterotrophically acquired micronutrients and accumulate manganese, magnesium and iron from the food. These metals are involved in photosynthesis and antioxidant protection. In addition, we show that fed corals can maintain high micronutrient concentrations in the host tissue during thermal stress and do not bleach, whereas unfed corals experience a significant decrease in copper, zinc, boron, calcium and magnesium in the host tissue and bleach. In addition, the significant increase in δ 65 Cu and δ 66 Zn signature of symbionts and host tissue at high temperature suggests that these isotopic compositions are good proxy for stress in corals. Overall, present findings highlight a new way in which coral heterotrophy and micronutrient availability contribute to coral resistance to global warming and bleaching. Abstract : We have studied the trophic ecology of micronutrients in a scleractinian coral submitted to thermal stress induced bleaching. Our results indicate that the copper (δ 65 Cu) and zinc (δ 66 Zn) isotopic signatures represent good proxies for stress in corals. They also reveal that symbionts are the major sink for micronutrients in the symbiotic association, and accumulate them from the heterotrophic feeding of the coral host. We finally showed that bleaching is exacerbated by micronutrient depletion in coral host tissue (especially copper, zinc, boron, magnesium) and that heterotrophic feeding can supply these essential elements to corals.